Maternal speech to singleton and first-born dizygotic twin infants: a four-month longitudinal and naturalistic study. Issue 3 (4th May 2023) - Kokkinaki, Theano; Markodimitraki, Maria; Vasdekis, Vassilis G.S.
ABSTRACT: We compared maternal speech in interactions of mothers with their firstborn dizygotic twin and singleton infants. Nine twins and nine singletons were video-recorded at home in spontaneous face-to-face interactions with their mothers, from the 2 nd to the 6 th month. Continuous micro-analysis revealed that there are more quantitative and qualitative similarities than differences between singleton and twin mothers' speech. Singleton and twin mothers are similar in the frequency of thematic sequences though duration of maternal speech favours singletons. Singleton mothers' speech favours infant emotion and attention thematic sequences. However, singleton and twin mothers responded similarly to the rest infant internal states. Twin, but not singleton, mothers' infant attention utterances differed at times when there are marked advances in the infants' attentiveness. These results are discussed in relation to the theory of innate intersubjectivity and the sensitivity that twin mothers, similarly to singleton mothers, express to the young infants' expressions.